ANALISIS KEMAMPUAN MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR FKIP UNIVERSITAS RIAU DALAM PENGUKURAN KELILING DAN LUAS BANGUN DATAR - Zetra Hainul Putra (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2013)
The purpose of this study is to analyze student teachers at Primary School Teacher Education of RiauUniversity in understanding the concepts of measurement perimeter and area. The reason in doingthis research is that many student teachers usually use formal formula in solving measurementperimeter and area. They will do the same thing when they teach Primary School Students, so thestudents will not know how the formula works. Design research was chosen as a method in gettingdata. The data were collected from 48 student teachers at Primary School Teacher Education of RiauUniversity. The result showed that six out of ten group of student teachers did not use partitioning inthe beginning of the lesson. They also made a mistake in measuring the perimeter of unstructuredshapes. After classroom discussion, 96% student teachers came to the idea of partitioning. It meansthat they realized the important of partitioning in measure the area of unstructured shapes.Key words: measurement perimeter and area, design research, partitioning, and unstructured shape.